High on creativity: The impact of social liberalization policies on innovation - Vakili, Keyvan; Zhang, Laurina (Strategic Management Journal, 2018)
[Research summary: We use a large-sample inductive approach to explore the impact of two social liberalization policies (legalization of same-sex civil unions and medical marijuana) and one anti-liberalization policy (passage of abortion restrictions) on innovation. First, we show that liberalization policies increase state-level patenting, while the anti-liberalization policy reduces patenting. Next, we examine three possible mechanisms that could explain the findings. The results suggest that liberalization policies can increase the collaboration diversity of inventors, and hence, the rate, novelty, and impact of their innovation output, through promoting more liberal views and more openness to diversity. We also find speculative evidence that social liberalization policies increase entrepreneurial entry through promoting more diverse social interactions. We do not find evidence for liberal policies attracting top inventors from other regions. Managerial summary: How does the social context impact the rate and direction of innovation? This article examines this question by exploring the impact of two social liberalization policies (legalization of same-sex civil unions and medical marijuana) and one antiliberalization policy (passage of abortion restrictions) on innovation in the United States. We first show that liberalization policies increase patenting, while the anti-liberalization policy reduces patenting. Further analyses highlight the impact of these policies on individuals' openness to diversity as a driving mechanism. We show that inventors collaborate with more diverse partners after the implementation of liberalization policies, producing more innovations and more novel and impactful ones. We discuss the implications for firm location decisions, the impact of corporate social responsibility on innovation, and sources of regional competitive advantage.]